Is the lower atmosphere a readily accessible reservoir of culturable, antimicrobial compound-producing Actinomycetales? - Carolyn F. Weber; Jason T Werth (Frontiers in Microbiology, 2015)
Recent metagenomic studies have revealed that microbial diversity in the atmosphere rivals that of surface environments. This indicates that the atmosphere may be worth bioprospecting in for novel microorganisms, especially those selected for by harsh atmospheric conditions. This is interesting in light of the antibiotic resistance crisis and renewed interests in bioprospecting for members of the Actinomycetales, which harbor novel secondary metabolite-producing pathways and produce spores that make them well suited for atmospheric travel. The latter leads to the hypothesis that the atmosphere may be a promising environment in which to search for novel Actinomycetales. Although ubiquitous in soils, where bioprospecting efforts for Actinomycetales have been and are largely still focused, we present novel data indicating that culturable members of this taxonomic order are 3 to 5.6 times more abundant in air samples collected at 1.5, 4.5, 7.5 and 18 m above the ground, than in the underlying soil. These results support the hypothesis that mining the vast and readily accessible lower atmosphere for novel Actinomycetales in the search for undescribed secondary metabolites, could prove fruitful.